The indirect effect of self-concealment on distress through psychological inflexibility in Asian American, Black American, and White American college students. (1st May 2018) - Mendoza, Hadrian; Tully, Erin C.; Goodnight, Bradley; Gray, Jackson; Masuda, Akihiko
Abstract: The present cross-sectional study examined whether self-concealment was associated with general psychological distress, somatization, depression, and anxiety among Asian American, Black American, and White American college students in the U.S., and whether psychological inflexibility partially explains these associations. Participants ( N  = 991, 77% female, age range = 16–60 years) completed self-report measures of interest online. Results revealed the relations between self-concealment and the four distress variables in each ethnic group and suggested that these relations were explained partially through psychological inflexibility. Future research should examine this model among subpopulations of these ethnic groups, as well as the influence of various cultural variables. Highlights: Self-concealment (SC) is a well-recognized maladaptive psychological process. SC was known to be associated with various distress variables Asian American and Black Americans are understudied groups in SC research The present study revealed the associations between SC and distress in these understudied groups Psychological inflexibility partially explained these associations.